1985
DOI: 10.1038/315498a0
|View full text |Cite
|
Sign up to set email alerts
|

Substance P raises neuronal membrane excitability by reducing inward rectification

Abstract: Much interest has recently centred on the properties of peptides that modulate the excitability of nerve cells. Such compounds include the undecapeptide substance P, which is particularly well established as an excitatory neurotransmitter, and we examine here its effects on magnocellular cholinergic neurones taken from the medial and ventral aspects of the globus pallidus of newborn rats and grown in dissociated culture. These neurones have previously been shown to respond to substance P3 and are analogous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
115
1
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(139 citation statements)
references
References 26 publications
22
115
1
1
Order By: Relevance
“…Thus, functions of the ganglia were analyzed by examining the production of NADPH diaphorase and substance P in the neuronal cells. NADPH diaphorase is identical to nitric oxide synthase (26)(27)(28)(29) and nitric oxide functions as an inhibitory neurotransmitter to relax smooth muscle (30), while substance P is an excitatory neurotransmitter to contract circular smooth muscles (31,32). NADPH diaphorase positive neuronal cells were dense in the proximal colon of Ncx Ϫ / Ϫ mice with (data not shown) or without megacolon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, functions of the ganglia were analyzed by examining the production of NADPH diaphorase and substance P in the neuronal cells. NADPH diaphorase is identical to nitric oxide synthase (26)(27)(28)(29) and nitric oxide functions as an inhibitory neurotransmitter to relax smooth muscle (30), while substance P is an excitatory neurotransmitter to contract circular smooth muscles (31,32). NADPH diaphorase positive neuronal cells were dense in the proximal colon of Ncx Ϫ / Ϫ mice with (data not shown) or without megacolon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…current in cholinergic neurons of basal nucleus, which raises excitability of the neurons [13][14][15]. Because both intracellular ATP and phosphorylation were reported to be essential to maintain IRK1 channel activity [16], IRKs can be targets of protein kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of K + currents results in an increase of neuronal cellular excitability by decreasing resting membrane potential, increasing the action potential duration and reducing afterhyperpolarization. It has been reported that substance P and thyrotropin-releasing hormone inhibit neuronal inwardly rectifying K + current [19][20][21]. This inhibition is not voltage-dependent, and involves PTX-insensitive G proteins and protein kinase C activation in their signalling.…”
Section: Discussionmentioning
confidence: 99%